"Living Fossils": The Politics of Language Preservation in Huangshan, China. (7th October 2021) - Ingebretson, Britta
Abstract : This article examines the politics of language maintenance in Huangshan, China, home of the Huizhou topolects. I show how, under the guise of celebrating local heritage, local language documentation efforts encourage language demise through preemptive eulogization, the act of portraying a language or culture as being more moribund than it is. This has the effect of hastening language loss by portraying it as inevitable and already well underway. I argue that intentional or unintentional acts of preemptive eulogization may be quite prevalent in minority language efforts worldwide and may help explain the lack of success of language protection projects.